Hepatitis B Virus–Upregulated LNC‐HUR1 Promotes Cell Proliferation and Tumorigenesis by Blocking p53 Activity. Issue 6 (19th September 2018) - Liu, Ningning; Liu, Qi; Yang, Xiaohai; Zhang, Fang; Li, Xinda; Ma, Yuanwu; Guan, Feifei; Zhao, Xin; Li, Zhiwei; Zhang, Lianfeng; Ye, Xin
Abstract : Recent studies have indicated that a number of long noncoding RNAs (lncRNAs) are dysregulated in hepatocellular carcinoma, while their aberrant expressions are associated with tumorigenesis and poor prognosis. To identify hepatitis B virus (HBV)‐related lncRNAs, we used RNA deep sequencing to quantify the abundances of lncRNAs in HepG2 cells and HBV transgenic HepG2‐4D14 cells. Here, we demonstrate that lnc‐HUR1 is significantly upregulated in HepG2‐4D14 cells. We found that HBV‐encoded hepatitis B x protein can enhance the transcription of lnc‐HUR1. Overexpression of lnc‐HUR1 promotes cell proliferation, whereas knockdown of lnc‐HUR1 inhibits cell growth. We identified that lnc‐HUR1 can interact with p53 and inhibit its transcriptional regulation on downstream genes, such as p21 and B cell lymphoma 2–associated X protein. We generated lnc‐HUR1 transgenic mice and performed the partial hepatectomy (PHx) to examine liver regeneration. The data showed that the ratio of liver weight to body weight in lnc‐HUR1 transgenic mice is higher than that in wild‐type (WT) littermates at day 2 and day 3 following hepatectomy. Consistently, the results of bromodeoxyuridine staining on liver sections following hepatectomy indicate that the ratio of bromodeoxyuridine‐positive cells in lnc‐HUR1 transgenic mice is significantly higher than that in WT mice, suggesting that lnc‐HUR1 promotes cell proliferation during liver regeneration. Next, we performed the experiment of diethylnitrosamine‐induced tumorigenesis. The data demonstrate that tumor number in lnc‐HUR1 transgenic mice is higher compared with control mice, indicating that lnc‐HUR1 enhances diethylnitrosamine‐induced tumorigenesis. Conclusion: We reveal that HBV‐upregulated lnc‐HUR1 promotes cell proliferation and tumorigenesis by interacting with p53 to block downstream gene transcription. Our findings suggest that lnc‐HUR1 plays an important role in HBV‐related hepatocellular carcinoma development and may serve as a therapeutic marker for hepatocellular carcinoma. (Hepatology 2018; 00:000‐000).